Analisis Yuridis Tindak Pidana Cyberbullying Berdasarkan Pada Undang- Undang ITE dan Kitab Undang Undang Hukum Pidana - Putri wilujeng (Jurnal Hukum Lex Generalis, 2024)
Cyberbullying in Indonesia with 45% of children becoming victims according to UNICEF (2022) and 49% of internet users experiencing harassment on social media according to APJII. Effective prevention requires strong policies, victim support, a safe environment, and strong law enforcement. Increasing public awareness and education about the impact of cyberbullying is also crucial. The development of technology and social media, cyberbullying has a serious impact on the mental health of victims, and can give rise to power dynamics in the form of intimidation. This research uses a normative juridical approach to analyze this problem. This research shows that cyberbullying can be categorized as a criminal act based on articles that regulate defamation and insults.